A Multicenter Outcomes Analysis of Children With Severe Rhino/Enteroviral Respiratory Infection*. Issue 2 (February 2015) - Spaeder, Michael C.; Custer, Jason W.; Miles, Alison H.; Ngo, Lisa; Morin, Nicholas P.; Scafidi, Susanna; Bembea, Melania M.; Song, Xiaoyan
<x xml:space="preserve">Abstract</x> Objectives: To investigate the impact of human rhino/enteroviruses on morbidity and mortality outcomes in children with severe viral respiratory infection. Design: Retrospective cohort study. Setting: The ICU, either PICU or cardiac ICU, at three urban academic tertiary-care children's hospitals. Patients: All patients with laboratory-confirmed human rhino/enteroviruses infection between January 2010 and June 2011. Interventions: We captured demographic and clinical data and analyzed associated morbidity and mortality outcomes. Measurements and Main Results: There were 519 patients included in our analysis. The median patient age was 2.7 years. The median hospital and ICU lengths of stay were 4 days and 2 days, respectively. Thirty-four percent of patients had a history of asthma, and 25% of patients had a chronic medical condition other than asthma. Thirty-two percent of patients required mechanical ventilation. Eleven patients (2.1%) did not survive to hospital discharge. The rate of viral coinfection was 12.5% and was not associated with mortality. Predisposing factors associated with increased mortality included immunocompromised state (p < 0.001), ICU admission severity of illness score (p < 0.001), and bacterial coinfection (p = 0.003). Conclusions: There is substantial morbidity associated with severe respiratory infection due to human rhino/enteroviruses in children. Mortality was less severe than reported in other respiratory viruses such as influenza and respiratory syncytial virus. The burden of illness from human rhino/enteroviruses in the ICU in terms of resource utilization may be considerable.